A study of libraries in selected private hospitals in Quezon City - Fajardo, Cynthia Mae Manalaysay, 1946-
In line with the findings of this study, this thesis presents the Minimum Standards for Libraries in Philippine Hospitals with Bed Capacities of 100-125 as its major recommendation. A list of classification schemes for hospital libraries found in the chapter on technical services, and suggestive standard lists for building collections in the chapter devoted to historical background might be helpful to medical and hospital librarians.
It is hoped that this study will serve as an opening wedge for more studies along this line which could contribute to the improvement of Philippine hospitals, in general, and of Philippine hospital libraries, in particular.
This study has been undertaken to look into the state of hospital libraries in the selected area to bring out their most outstanding characteristics. This also proved useful in the formulation of detailed standards geared to the Philippine setting.
This study shows that there are two general types of libraries connected with hospitals: the medical and the nursing. The nursing libraries, being the only libraries connected with these hospitals, inadequately serves the medical staff. The absence of real medical libraries is noted. Although it seems that the hospital libraries differed quite significantly from each other, there are more striking similarities existing among the nursing libraries than among the medical libraries.
This thesis is a survey of six libraries in private general/general-teaching-training hospitals with bed capacities of a hundred or more in Quezon City. By means of a questionnaire, interviews, and actual observation of the libraries, the following were considered: administration, finance, collections, technical services, library quarters and facilities, and readers' services and use of the library.
When the libraries are gauged against the existing British, American, and Philippine standards, they come closer to the Philippine standards which are brief and generalized rather than to the detailed and specific requirements of the British and American standards. The libraries, as gauged against the Philippine standards, need improvement in their collections and physical facilities. They do not meet the British and American standards in their organization and management, the coverage of their collections, services, and their physical facilities and equipment. The majority of the libraries are found to have financial difficulties.
Thesis (M.L.S.)--University of the Philippines, Diliman
Typescript.
Vita
Keywords: Hospital libraries--Philippines--Quezon City